2021
DOI: 10.3389/fnagi.2020.621947
|View full text |Cite
|
Sign up to set email alerts
|

NeuroExercise: The Effect of a 12-Month Exercise Intervention on Cognition in Mild Cognitive Impairment—A Multicenter Randomized Controlled Trial

Abstract: Exercise intervention studies in mild cognitive impairment (MCI), a prodromal stage of Alzheimer's disease (AD), have demonstrated inconsistent yet promising results. Addressing the limitations of previous studies, this trial investigated the effects of a 12-month structured exercise program on the progression of MCI. The NeuroExercise study is a multicenter randomized controlled trial across three European countries (Ireland, Netherlands, Germany). Hundred and eighty-three individuals with amnestic MCI were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…The multiple significant associations between other covariates and mobility in the repeated-measures mixed models investigating cognitive functions as predictors, suggest that there may be scope for interventions to slow down adverse trajectories of mobility decline even in the presence of baseline cognitive impairment, by acting on potentially modifiable factors (e.g., improving muscle strength, addressing fear of falling, optimising medications). Intervention approaches including physical exercise may also be appropriate [57][58][59], although not necessarily effective in improving cognition [60]. Indeed, in community-based samples, comprehensive geriatric assessment and individuallytailored interventions may contribute to improvements in the health and functional status of older persons with multimorbidity [61].…”
Section: Discussionmentioning
confidence: 99%
“…The multiple significant associations between other covariates and mobility in the repeated-measures mixed models investigating cognitive functions as predictors, suggest that there may be scope for interventions to slow down adverse trajectories of mobility decline even in the presence of baseline cognitive impairment, by acting on potentially modifiable factors (e.g., improving muscle strength, addressing fear of falling, optimising medications). Intervention approaches including physical exercise may also be appropriate [57][58][59], although not necessarily effective in improving cognition [60]. Indeed, in community-based samples, comprehensive geriatric assessment and individuallytailored interventions may contribute to improvements in the health and functional status of older persons with multimorbidity [61].…”
Section: Discussionmentioning
confidence: 99%
“…RCTs with participants with memory complaints or MCI and no definition of SVD at enrolment (NeuroExercice, AIBL Active) have found no intervention effects of aerobic exercise on cognitive or imaging outcomes. 113,114 However, an RCT with elderly individuals at-risk for dementia from the general population (FINGER) has shown that a multidomain intervention including diet, exercise, cognitive training and vascular risk monitoring has beneficial effects in improving and maintaining…”
Section: Additional Informationmentioning
confidence: 99%
“…RCTs with participants with memory complaints or MCI and no definition of SVD at enrolment (NeuroExercice, AIBL Active) have found no intervention effects of aerobic exercise on cognitive or imaging outcomes. 113 , 114 However, an RCT with elderly individuals at-risk for dementia from the general population (FINGER) has shown that a multidomain intervention including diet, exercise, cognitive training and vascular risk monitoring has beneficial effects in improving and maintaining cognitive functioning. 115 A pooled analysis of 322 individuals from two RCTs targeting lifestyle and vascular risk factors with multi-domain interventions to prevent post-stroke cognitive impairment found limited evidence of benefit on attention but not on other cognitive domains.…”
Section: Additional Informationmentioning
confidence: 99%
“… 2 NeuroExercise screened 1528 individuals over 18 months, including 835 (54.6%) deemed ineligible at screening. 2 , 18 In another 12‐month RCT of home‐based aerobic exercise in adults with aMCI, a total of 1620 individuals were screened, including 1550 (95.7%) who did not meet eligibility criteria over a 4‐year recruitment period. 19 EXERT experienced greater recruitment success, with screen failure rates of 46.1% and 44.7% after telephone and in‐person screening visits, respectively, during 3.5 years of recruitment.…”
Section: Discussionmentioning
confidence: 99%